2017
DOI: 10.15666/aeer/1504_031048
|View full text |Cite
|
Sign up to set email alerts
|

Use of Black Seed (Nigella Sativa L.) Oil in the Management of Hypertensive and Hyperlipidemic Individuals of District Muzaffarabad, Azad Kashmir, Pakistan

Abstract: Abstract. Hypertension and hyperlipidemia are two main causes of cardiovascular diseases with rapidly increasing pervasiveness worldwide. Complimentary alternative medicines provide an effective choice to these highly prevalent global health issues. Nigella sativa has diverse range of traditional and pharmacological potential with established safety profile. This study was carried out in 163 mildmoderate hypertensive and hyperlipidemic patients. Patients were selected randomly of both genders. The patient's ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Hussain et al demonstrated that the consumption of virgin Nigella sativa oil at the dose of 1 mL/day in 146 mild-moderate hypertensive and hyperlipidemic patients for 45 days significantly reduced systolic (SBP) and diastolic blood pressure (DBP) (p < 0.05) as compared to the baseline. Regarding the lipid profile, the supplement produced a significant decrease in total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglycerides (Tg) and an increase in high-density lipoprotein cholesterol (HDL-C) (p < 0.05 for all) compared to initial values [26].…”
Section: Cardio-protective and Anti-hypertensive Activitiesmentioning
confidence: 94%
“…Hussain et al demonstrated that the consumption of virgin Nigella sativa oil at the dose of 1 mL/day in 146 mild-moderate hypertensive and hyperlipidemic patients for 45 days significantly reduced systolic (SBP) and diastolic blood pressure (DBP) (p < 0.05) as compared to the baseline. Regarding the lipid profile, the supplement produced a significant decrease in total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglycerides (Tg) and an increase in high-density lipoprotein cholesterol (HDL-C) (p < 0.05 for all) compared to initial values [26].…”
Section: Cardio-protective and Anti-hypertensive Activitiesmentioning
confidence: 94%
“…Qidwai et al (2009) black nigella seeds contain bioactive components like thymol that could reduce blood pressure by blocking calcium channels (Ramadan, 2007). Black cumin oil (0.5 mL/twice a day/45 days) decreased systolic blood pressure and diastolic blood pressure in subjects with mild to moderate hypertension (Hussain et al, 2017). Doses of the volatile oil of N. sativa (4-32 µL/kg) administered intravenously to urethane-treated rats significantly reduced the heart rate and systemic arterial pressure (El Tahir et al, 1993).…”
Section: Antihypertensive Activity Of Nigella Sativamentioning
confidence: 99%
“…However, in a randomized controlled clinical trial in elderly patients with hypertension, black cumin administration (300 mg black cumin seed extract twice daily for 28 days) showed a slight but insignificant reduction in blood pressure [ 146 ]. On the contrary, a clinical study on patients with mild–moderate hypertension using black cumin virgin oil demonstrated positive outcomes on lipid profiles and blood pressure [ 147 ]. With the evidence stated here and in the previous sections, it can be anticipated that black cumin can be a promising candidate for developing therapeutics against heart diseases, provided that the controversies raised in some studies are properly resolved by employing appropriate experimental models.…”
Section: Benefits Of Black Cumin On Human Health and Disease Conditionsmentioning
confidence: 99%